Synegistic effects of zinc oxide in intumescent flame retardant silicone rubber composites - Jiao C; Chen X; Zhuo J (Plastics,Rubber and Composites, 2013)
The synergistic effects of zinc oxide(ZnO) with intumescent flame retardant(IFR; based on phosphorus acid, melamine pentaerythritol) in silicone rubber(SR) composites have been studied using limiting oxygen index, UL-94, cone calorimeter test and digital photographs.The results showed that 2.0 wt-;loading ZnO in the flame retardant SR composites could greatly reduce the peak values of heat release rate and smoke production rate, and form a compact char layer on the surface of the sample. Thus, a suitable amount of ZnO plays a synergistic effect with IFR in flame retardant SR composites system.
Keywords: Flame retardant; IFR; Silicone rubber; ZnO